The Correlations between Cord Blood Leptin and Leptin Level at Six Months with Infant Growth - Ika Rara Rosita; Agustini Utari; Maria Mexitalia (Faculty of Medicine, Diponegoro University, 2021)
Background: Leptin plays an important role in regulating body weight, metabolism, and reproductive functions. Leptin affects metabolism by reducing nutrient intake and increasing energy expenditure which eventually also plays a role in infant growth.Objective: This study aims to determine the relationship between leptin levels and infant growth age 0-6 months.Methods: A prospective cohort study was done for six months on 38 infants, age 0-6 months, from breastfeeding mothers with normal pregnancies. The samples were taken twice, firstly when the infant was born using an umbilical cord blood sample, and secondly at the age of six months, using a vein blood sample. Serum leptin levels were measured using the ELISA method. Infant growth was assessed using WHO 2005’s z-scores.Results: A total of 50 babies were included in the study, 38 of them had been studied completely. Significant correlations were found between the mean of the umbilical cord and six months of age leptin levels (p <0.001), between delta leptin with WHZ and delta leptin with WAZ at six months of age (p = 0.002 and p = 0.003, respectively), and between leptin levels with WHZ (p<0.001) and leptin levels with WAZ (p = 0.004) at six months of age. Leptin levels at the age of six months are lower than umbilical cord blood leptin. Conclusion: The greater decrease of leptin level in the first six months is associated with better infant growth.